2022
DOI: 10.3390/cells11061027
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Bioreactor for Reconstitution of the Epithelium and Submucosal Glands in Decellularized Ferret Tracheas

Abstract: Tracheal grafts introduce the possibility to treat airway pathologies that require resection. While there has been success with engraftment of the surface airway epithelium (SAE) onto decellularized tracheas, there has been minimal advancement in regenerating the submucosal glands (SMGs). We designed a cost-effective open-system perfusion bioreactor to investigate the engraftment potential of ferret SAEs and murine myoepithelial cells (MECs) on a partly decellularized ferret trachea with the goal of creating a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…To better understand the factors that influence the efficiency of cell engraftment, we assessed the differences in the transcription of cell adhesion related genes between Tomato+ cells seeded on a denuded tracheal graft and an ECM-coated cell culture dish. To this end, we removed the SAE from freshly excised tracheas using a series of SDS-containing detergent washes as described previously ( 24 ). Then, we engrafted 10 7 p6 Tomato+ primary surface airway basal cells into a 3-cm ferret tracheal segment using a rotating bioreactor method developed by our group previously for ferret tracheal explant cultures ( 24 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To better understand the factors that influence the efficiency of cell engraftment, we assessed the differences in the transcription of cell adhesion related genes between Tomato+ cells seeded on a denuded tracheal graft and an ECM-coated cell culture dish. To this end, we removed the SAE from freshly excised tracheas using a series of SDS-containing detergent washes as described previously ( 24 ). Then, we engrafted 10 7 p6 Tomato+ primary surface airway basal cells into a 3-cm ferret tracheal segment using a rotating bioreactor method developed by our group previously for ferret tracheal explant cultures ( 24 ).…”
Section: Resultsmentioning
confidence: 99%
“…To this end, we removed the SAE from freshly excised tracheas using a series of SDS-containing detergent washes as described previously ( 24 ). Then, we engrafted 10 7 p6 Tomato+ primary surface airway basal cells into a 3-cm ferret tracheal segment using a rotating bioreactor method developed by our group previously for ferret tracheal explant cultures ( 24 ). After 18 h, the explants were rigorously washed with PBS to remove any cells that did not fully engraft, and then the luminal surface of the tracheas was brushed to collect Tomato+ cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding respiratory epithelial cell growth, this is best achieved with an air-liquid-interface. [94,95] On the other hand, different culture conditions are required for neovascularization and promotion of cartilage maturation of the tracheal rings, pointing to the need to optimize unique bioreactor systems to promote multitissue development. Moreover, the need for neovascularization of in vitro cultured tissue limits the size and thickness of engineered constructs.…”
Section: Post-bioprintingmentioning
confidence: 99%
“…In a recent publication, our group introduced a novel bioreactor capable of partially decellularizing the luminal compartment of a ferret trachea and of supporting implanted allogeneic surface airway epithelial (SAE) basal cells (BCs). Furthermore, we demonstrated that establishing an air-liquid interface within the bioreactor promoted early differentiation of the SAE BCs [5]. In this article, we orthotopically transplanted these bioengineered tracheas and tracked the contribution of fluorescent airway stem cells.…”
Section: Introductionmentioning
confidence: 99%